2019
DOI: 10.4067/s0717-95022019000401220
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric Characteristics, Body Composition and Somatotype of Elite Pan-American Race Walking 20K

Abstract: The anthropometric and somatotype evaluation is an essential tool in the selection and control of high-performance athletes. The aim of this study was to describe the somatotype and body composition of male elite race walkers (20 k modality), and its relationship with athletic performance. Twenty-four race walkers participated in this study. The sample was divided into two groups: the race walkers with the best performance (upper 25 percentile; n=7) and the second group (n=17) that corresponds to the rest of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
0
5
0
2
Order By: Relevance
“…Somatotype role and performance in ultra trail runners. Journal of Sport Sciences Researches,6(2),[269][270][271][272][273][274][275][276][277][278] 274 ©JSSR runners. While there was a significant negative relationship between running distance and endomorph (r = -.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Somatotype role and performance in ultra trail runners. Journal of Sport Sciences Researches,6(2),[269][270][271][272][273][274][275][276][277][278] 274 ©JSSR runners. While there was a significant negative relationship between running distance and endomorph (r = -.…”
Section: Resultsmentioning
confidence: 99%
“…In another study showing the relationship between the somatotypes and body composition with athletic performance of 20 km Pan-American elite male walkers, it was found that the somatotype of the best performing athletes was 2.5-3.8-2.9 while it was 2-2.8-4.1 for the lowest performing athletes. It was stated that ectomorphic feature and height are morphological features that can determine the athletic performance (Espinoza-Navarro, Lizana, Gómez-Bruton, Brito-Hernández & Lagos-Olivos, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…El estudio de la estructura física de atletas cada vez más gana interés en las investigaciones en la ciencia del deporte (Espinoza-Navarro, et al, 2019;Cavedon, et al, 2018;Vaquera, et al, 2015). A través de evaluaciones especificas es posible definir un perfil ideal de composición corporal y somatotipo para una determinada modalidad deportiva visando por ejemplo la selección y el control del alto rendimiento de atletas, lo que aumentaría las oportunidades de logros deportivos (Medeiros, et al, 2016).…”
Section: Introductionunclassified
“…Komposisi tubuh dan somatotype menjadi salah satu unsur keberhasilan olahraga(Dwiyanti et al 2020)(Çinarli and Kafkas 2019;Drywień et al 2021;Gutnik et al 2015;Roklicer et al 2020), kinerja fisik(Quintero et al 2019), dan banyak cabang olahraga dengan karakteristik antropometri merupakan hal yang sangat penting(Blerim et al 2018;Espinoza- Navarro et al 2019;Perroni et al 2015;Petković et al 2019). Penelitian yang dilakukan oleh(Sukmawarti, Akbar, and Doewes 2019) adanya hubungan antara somatotype dan passing accuracy yang signifikan pada pemain futsal .…”
unclassified